Premières impressions sur l'Exposition universelle de Shanghai - Florence Padovani (EchoGéo)
First the article explains what are the different processes to organize a World Exposition, then it shows that in Shanghai it was done in such a way that the emphasis was more on China facing its own history and its own population rather than China facing the world. « Shanghai Expo 2010 » was a huge popular fair which did not provide many hints for the future urban planning.